Antiepileptic drugs: Role in paediatric poisoning. (2nd January 2018) - Ferranti, Silvia; Grande, Elisabetta; Gaggiano, Carla; Grosso, Salvatore
Abstract : Intoxications, both accidental and intentional, are common in children and adolescents and often require hospitalisation and intensive treatment. Antiepileptic drugs are a possible cause of poisoning and intoxications because this category of medications has shown a rising trend in recent years. They might be responsible for multi‐organ dysfunctions of variable severity, ranging from subtle symptoms to life‐threatening complications. No guidelines on the management of these intoxications in the paediatric population are currently available, and treatment is mainly supportive. Activated charcoal administration and extracorporeal circulation techniques for drug removal have been proposed. Facing the complexity of this clinical scenario, it is of utmost importance to maintain a high index of suspicion to guarantee a prompt intervention and ensure the best possible management for the patient.